1995
DOI: 10.1089/thy.1995.5.125
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Thyrotoxicosis: A Case Report and Recommendations for Prediction, Diagnosis, and Treatment

Abstract: A maternal history of Graves' disease places the fetus at risk for thyrotoxicosis in utero via the placental transfer of thyroid-stimulating immunoglobulins. Methods for prediction of fetal hyperthyroidism are available, but are not widely used. Clinical assessment of fetal thyroid status by monitoring of fetal heart rate and growth may be inaccurate. This raises some uncertainty in the initial diagnosis of fetal thyrotoxicosis and complicates the assessment of fetal response to maternal propylthiouracil thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…Therefore, the threshold value of TSAb needs to be confirmed in a larger study with a bioassay performed in every mother with detectable TBII level during pregnancy. However, our data are concordant with the literature: levels of TSAb reported to be predictive of neonatal hyperthyroidism were a stimulation of cAMP over 350-500% in T3 (10,25,27,30) or over 500% in T2 (31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the threshold value of TSAb needs to be confirmed in a larger study with a bioassay performed in every mother with detectable TBII level during pregnancy. However, our data are concordant with the literature: levels of TSAb reported to be predictive of neonatal hyperthyroidism were a stimulation of cAMP over 350-500% in T3 (10,25,27,30) or over 500% in T2 (31).…”
Section: Discussionsupporting
confidence: 92%
“…Individual cases are shown in Table 2. The median age of the women at the beginning of pregnancy was 31 years (range, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Twenty mothers of 21 neonates (one twin pregnancy) had a past history of GD.…”
Section: Clinical Characteristics Of the Mothersmentioning
confidence: 99%
“…The remaining 27 women who gave birth to euthyroid infants showed TRAb1 values of below 40 U/L. It is also pointed out by Laurberg et al [7] and Wallace et al [8] that with TRAb1 method of TRAK (Brahms, Berlin, Germany) the levels above approximately 40 U/L are considered high enough to indicate risk of neonatal hyperthyroidism. Interestingly, Momotani reported that the levels above 50% of TRAb1 (Cosmic corporation, Tokyo, Japan) are useful for the prediction of NH and the data obtained from the literature by Matsuura et al [4] and Hale et al [5] strongly supported the view hat positive TRAb1 >50% conveyed high likelihood of NH.…”
Section: Discussionmentioning
confidence: 89%
“…It has thus been recommended to determine TRAb late in pregnancy in women with GD to predict the risk of neonatal hyperthyroidism (NH). An arbitrary limit of 50% [3][4][5] or 40 U/L [6][7][8] using 1st generation TRA (TRAb1) assay was suggested to indicate risk when measured late in pregnancy. In order to substitute TRAb1 assay with the 2nd generation TRAb assay using porcine TSH receptor (pTRAb2) and human recombinant TSH receptor (hTRAb2) and the 3rd generation TRAb (TRAb3) assay, we measured TRAb in these four methods late in pregnancy.…”
mentioning
confidence: 99%
“…Thus they cross the placenta more readily. Conversely, the effect of PTU in the fetus is heightended by a slow fetal clearance of this drug [27], Doses of PTU between 200 and 600 mg have been reported [3,6,8,21,28]. Carbimazole is used less than PTU.…”
Section: Discussionmentioning
confidence: 99%